2021
DOI: 10.3390/agriculture11040293
|View full text |Cite
|
Sign up to set email alerts
|

European Dairy Farmers’ Perceptions and Responses towards Development Strategies in Years of Turbulent Market and Policy Changes

Abstract: Farmers operate in a changing market, policy and social environment so questions arise as to how they experience these changes and react in their business orientation. This topic was examined in the period 2011 to 2016 in a strongly fluctuating product market and food policy environment, e.g., abolition of milk quotas in Europe. The study was based on unique panel data for 290 dairy farms in Poland, Slovenia, Lithuania and The Netherlands, questioned up to three times in 2011, 2013 and 2016. The conceptual fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
(58 reference statements)
0
3
0
Order By: Relevance
“…Finally, Areal et al [26], applying a Bayesian stochastic frontier analysis on English and Welsh farm data from 2000 to 2005 to investigate the relationship between milk quotas and technical efficiency, supported the idea that abolishing the milk quota leads to a more competitive market for milk, which forces the least-efficient farms to leave milk production. The abolition of a milk quota brought a high expectation for farmers [32]. Its elimination has had an effect on the whole dairy sector [33,34].…”
Section: Of 21mentioning
confidence: 99%
“…Finally, Areal et al [26], applying a Bayesian stochastic frontier analysis on English and Welsh farm data from 2000 to 2005 to investigate the relationship between milk quotas and technical efficiency, supported the idea that abolishing the milk quota leads to a more competitive market for milk, which forces the least-efficient farms to leave milk production. The abolition of a milk quota brought a high expectation for farmers [32]. Its elimination has had an effect on the whole dairy sector [33,34].…”
Section: Of 21mentioning
confidence: 99%
“…Farmers after 2015, without the threat of paying a penalty for not having a milk quota, were able to increase their milk production. Dairy farms that had sufficient land resources necessary for roughage production increased the scale of milk production quite rapidly [27,28].…”
Section: Return On Equity In Average Dairy Farms From Selected Eu Cou...mentioning
confidence: 99%
“…A limited number of socio-economic investigations have been conducted on the profitability of the meat and poultry industries [36]. Undoubtedly, the value chain has moved from the farmer towards a retailer [37]. Along with other researchers [38], several authors have also found that the overall economic value of farmers' and meat and poultry processors' work are significantly less than the achieved production and costs incurred [39].…”
Section: Financial Efficiency In Terms Of Profitability In the Meat And Poultry Industriesmentioning
confidence: 99%